Pengaruh citra merek, persepsi kualitas produk dan persepsi harga pada kepuasan pelanggan serta dampaknya terhadap loyalitas pelanggan - Agustinus Dwi Kristianto; Triyono Arief Wahyudi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
The purpose of this study is to build a model that explains various interactions between brand image, perceived quality, perceive price, customer satisfaction, and customer loyalty as well as empirical proof of the model that has been developed. This study through a survey of 120 male and female respondents aged 17-50 years and has been consuming the product in the last 3 months. This study model will be analyzed using SEM and data from the survey is processed using SPSS 20. The result of the hypothesis test shows that there is significant influence between brand image, perceive of quality product and perceive price on customer satisfaction. Also, there is a significant influence on customer satisfaction on customer loyalty.